Planting method and tank-mix herbicides effects on weed management in garlic (Allium sativum) - HAJEBI, ABDOLHAMID; DAS, T K; VYAS, A K; RANA, D S (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was carried out at the Indian Agricultural Research Institute during 2012 and 2013 to investigate the effect of planting method and tank-mix herbicide application on weeds, and growth, yield and nutrient uptake of garlic (Allium sativa L.). It was observed that the flat (FB) and raised (Furrow-irrigated raised bed system; FIRBS) beds were comparable with each other on the density and dry weight of weeds, and plant height, yield and bulb diameter of garlic during both years. The pre-emergence tank-mix application of pendimethalin 0.75 kg/ha + imazethapyr 0.075 kg/ha was superior to all other herbicide treatments in reducing weed competition as well as the uptakes of N, P and K by weeds. The uptakes of N, P and K, and the bulb yield of garlic were considerably higher in weed-free check and the tank-mix pre-emergence application of pendimethalin 0.75 kg/ha + imazethapyr 0.075 kg/ha compared to other treatments. The pendimethalin 0.75 kg/ha + imazethapyr 0.075 kg/ha and weed-free check brought about increases in two-year mean garlic bulb yield by 244.4% (~2.4 times) and 264.2% (~2.6 times), respectively over weedy check.